2014
DOI: 10.1080/03075079.2014.968543
|View full text |Cite
|
Sign up to set email alerts
|

Power and control: managing agents for international student recruitment in higher education

Abstract: professional practice. The themes arising from the interviews were (1) emphasis on broader, transferable skills rather than specific skills; (2) approach to work undergirded competencies;(3) importance of understanding contexts; (4) knowledge of assessment; (5) ability to adapt to different audiences; and (6) ability to apply content. These themes affirm the generalist preparation offered by most student affairs graduate programs. (49 ref)-Iowa State University. West, Nicole M. A Decade of a Student Affairs Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 57 publications
1
74
0
1
Order By: Relevance
“…Moreover, a similar analysis of other dimensions of education agent management, such as selection, contracting, and training would further improve the understanding of best practices in this industry. Government, 2010;Bridge Education Group, 2016;Coco, 2015;Coffey & Perry, 2013;Di Maria, 2014;Galbraith & Brabner, 2013;Guest & Gregory, 2017;Huang et al, 2016;ICAC, 2004ICAC, , 2015Marcus, 2013;Marsh, 2016;Newell & Watt, 2012;Pattingale, 2007;PhillipsKPA, 2005;Productivity Commission, 2015;Raimo et al, 2015;Reisberg & Altbach, 2011;Roy, 2017;Stecklow & Harney, 2016;Tamar, 2008;Tan, 2015;West & Addington, 2014 Misinformation includes any situation where wrong or incomplete information is accidentally given to students. This may occur because of lack of effort to acquire the right information, incomplete training or misunderstanding (c.f.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a similar analysis of other dimensions of education agent management, such as selection, contracting, and training would further improve the understanding of best practices in this industry. Government, 2010;Bridge Education Group, 2016;Coco, 2015;Coffey & Perry, 2013;Di Maria, 2014;Galbraith & Brabner, 2013;Guest & Gregory, 2017;Huang et al, 2016;ICAC, 2004ICAC, , 2015Marcus, 2013;Marsh, 2016;Newell & Watt, 2012;Pattingale, 2007;PhillipsKPA, 2005;Productivity Commission, 2015;Raimo et al, 2015;Reisberg & Altbach, 2011;Roy, 2017;Stecklow & Harney, 2016;Tamar, 2008;Tan, 2015;West & Addington, 2014 Misinformation includes any situation where wrong or incomplete information is accidentally given to students. This may occur because of lack of effort to acquire the right information, incomplete training or misunderstanding (c.f.…”
Section: Discussionmentioning
confidence: 99%
“…This may occur because of lack of effort to acquire the right information, incomplete training or misunderstanding (c.f. Huang et al, 2016;ICAC, 2015;PhillipsKPA, 2005). On the other hand, disinformation refers to intentional misleading of students (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agents are an influential factor in students' decision-making, as well as in universities' success in attracting high numbers of international students (Huang, Raimo, & Humfrey, 2014;Mazzarol & Soutar, 2012;O'Connell & Wong, 2014). A 2011 British Council report found that "…48% of interviewed East Asian students had contacts with an agent, compared to 41% in Africa, 39% in South Asia, 30% in Latin America, and 23% in Europe" (ACA, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This has translated into the active development of strategies, policies, programmes and infrastructure that has made many universities into institutions that take internationalisation seriously. A variety of internationalisation policies and practices have been employed and developed in HEIs, on their home campuses and abroad, to implement their internationalisation plans, such as recruiting international students (Cudmore 2005;Mosneaga and Agergaard 2012;Huang, Raimo, and Humfrey 2016), internationalising the curriculum (Haigh 2002;Luxon and Peelo 2009;Ardakani et al 2011;Magne 2015;Pandian, Baboo, and Mahfoodh 2016), promoting international research mobility (Attila and Andrea 2009;Jacob and Meek 2013), integrating international students and promoting intercultural capabilities (Stier 2006;Miller 2014), and the opening up of branch campuses in other countries which are designed to attract students who are not able to travel overseas for education (Wilkins and Huisman 2012;"Overseas Branch Campuses" 2015;Wilkins and Huisman 2015;Shams and Huisman 2016).…”
Section: Internationalisation Agendas At Universitiesmentioning
confidence: 99%